Coleção Etnográfica - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2025)
In this volume you will discover a collection of handcrafted objects with unique characteristics, associated with the culture of traditional communities.
Ethnographic Collection
Keywords: Povos indígenas; Comunidades tradicionais; Amazônia; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA DAS POPULACOES AFRO-BRASILEIRAS